2002
DOI: 10.1177/154193120204602620
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Tendency, Feeling of Presence, and Simulator Sickness: Formulation of a Causal Model

Abstract: Three virtual environment (VE) constructs were studied and a model was generated to explain the relations among them. Data were gathered using the Immersive Tendency Questionnaire (ITQ), the Presence Questionnaire (PQ), and the Simulator Sickness Questionnaire (SSQ). The model was tested and modified using structural equation modeling (SEM) techniques. The results showed that the original hypothesized model did not fit the data very well (which is typical), but after respecification the model showed good fit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…Principal-components factor analysis is just one tool that may help to better understand the factors underlying the concept. Although less well known than factor analysis, structural equation modeling is another tool that may aid in discovering the relationships among the variables underlying presence, and perhaps also the relationship between presence and other variables such as simulator sickness, individual immersive tendencies, or performance (Jerome & Witmer, 2002). Measures of presence, including the PQ, must be tested and retested if we are to have confidence in their validity.…”
Section: Need For Additional Researchmentioning
confidence: 99%
“…Principal-components factor analysis is just one tool that may help to better understand the factors underlying the concept. Although less well known than factor analysis, structural equation modeling is another tool that may aid in discovering the relationships among the variables underlying presence, and perhaps also the relationship between presence and other variables such as simulator sickness, individual immersive tendencies, or performance (Jerome & Witmer, 2002). Measures of presence, including the PQ, must be tested and retested if we are to have confidence in their validity.…”
Section: Need For Additional Researchmentioning
confidence: 99%
“…The effectiveness of the system is thought to be linked to the sense of presence 9 as it allows the user to have a more meaningful, richer experience within the medium. It is hypothesised that the sense of presence is affected by a number of factors 9À11 that include: * the quality of the interface, * pictorial realism, * distraction, * task, * sensory fidelity, * subject involvement, * immersion, * cognitive style, Presence is thought to be inversely related to simulator sickness, 9 the subjects who have a greater involvement and immersion in the artificial 3D world having a tendency to experience less simulator sickness. The more sickness symptoms subjects experience the more distracted and less presence they will feel.…”
Section: Introductionmentioning
confidence: 99%
“…Presence, which can be defined as the extent to which the participants’ senses are engaged by the virtual world, is another important factor in the use of virtual environments. The effectiveness of the system is thought to be linked to the sense of presence 9 as it allows the user to have a more meaningful, richer experience within the medium. It is hypothesised that the sense of presence is affected by a number of factors 9 11 that include:the quality of the interface,pictorial realism,distraction,task,sensory fidelity,subject involvement,immersion,cognitive style,…”
Section: Introductionmentioning
confidence: 99%
“…If an individual experiences emotional reactions in a digital learning environment, they may engage in the learning process 42. Previous studies43 44 have also suggested that the tendency to experience sense of presence may depend on an individual’s personal characteristics. Witmer and Singer43 defined that immersion tendency is as an individual’s disposition to becoming involved in mediated environments.…”
Section: Conceptual Frameworkmentioning
confidence: 99%